COMPARATIVE IN- VITRO EVALUATION OF VANCOMYCIN MINIMUM INHIBITORY CONCENTRATIONBY AGAR DILUTION AND E-STRIP IN METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - Ilyas, Sheroze; Munir, Tehmina; Sadaf, Rabia; Gilani, Mehreen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the in-vitro efficacy by determining Minimum Inhibitory Concentration of Vancomycin using the reference Agar Dilution to the E-Strip in Methicillin Resistant Staphylococcus aureus isolates. Study Design: Validation study. Place and Duration of Study: The department of Microbiology Army Medical College/National University of Medical Sciences in collaboration with Pak Emirates Military Hospital Rawalpindi, from Dec 2016 to Dec 2017. Methodology: Non-duplicate 84 isolates of Methicillin resistant Staphylococcus aureus from various clinical specimens were included in the study. All these isolates were screened for susceptibility to glycopeptide by E-strips method (Bio mérieux) as well as Agar Dilution method, using vancomycin concentrations of 0.25, 0.50, 1.00, 2.00, 4.00 and 8.00µgm/ml respectively in two fold serial dilutions. Results: There was an overall agreement on 83 samples by both the methods i.e. 83 were Vancomycin Sensitive Staphylococcus aureus by both methods while one isolate with intermediate resistance to Vancomycin was only detected by Agar Dilution. The sensitivity of the E–strips compared to Agar Dilution was found to be 100%. The positive predictive value was 98.8% with a diagnostic accuracy of 98.8%. Specificity and negative predictive value could not be ascertained for E-strips because of the limitation of the method to detect the Vancomycin Intermediate Staphylococcus aureus isolates. Conclusion: E-strip can be a convenient alternative to the gold standard Agar Dilution but its inability to identify VISA challenges its reliability in determining the Vancomycin resistance in MRSA isolates.